Gender-based Education to Addressing Child Marriage - Sri Endah Kinasih; Mochamad Kevin Romadhona; Citra Hennida; Kandi Aryani Suwito; Alaa Basil Baqer Alfadhel (Universitas Negeri Semarang, 2025)
Indonesia has one of the highest child marriage rates in East Asia and the Pacific, with 27.8% of women marrying at a young age in East Java. This is despite the Sustainable Development Goals (SDGs) targets published in 2015 and 2030. In rural areas, access to education is uneven and lacking, particularly for women, who are burdened with various types of work and lack knowledge. Education is often seen as a long-term investment to eliminate backwardness and underdevelopment, but many members of society still believe that the social roles and functions of men and women are not the same. Gresik Regency, a district with rapid industrial sector development, has one of the highest poverty rates in East Java. Child marriage practices neglect the personal aspects of women and children's rights, such as survival, development, protection, and equal participation. This hinders women's empowerment due to economic issues, as the effort to marry off underage children is driven by the desire to lighten parents' burden. To address this issue, the Community Partnership Program proposal aims to create educational modules and videos for gender sensitive and information technology-oriented curriculum development to prevent child marriage among junior high school students in Gresik. The use of information technology, specifically the internet and social media, will be optimized to conduct literacy on the impact of child marriage.